Efek Penambahan Butanol Terhadap Emisi dan Temperatur Gas Buang Mesin Bensin EFI Menggunakan EGR - Lukman Sanjaya, Firman; Syarifudin, Syarifudin; Fatkhurrozak, Faqih (P3M Politeknik Negeri Cilacap, 2022)
The high octane number and oxygen content of butanol can improve combustion more completely and the residual gas resulting from engine combustion is more environmentally friendly. This study examines the effect of adding 5% to 15% butanol at 5% intervals on a gasoline engine with an EGR system with premium fuel on emissions and exhaust gas temperatures. The exhaust gas analyzer was used to measure the combustion gases. Exhaust gas temperature was measured using a thermocouple mounted on the exhaust manifold. The mixture of P85B15 reduced CO levels by 68.11% and HC by 37.50% compared to P100. However, CO2 emissions and exhaust gas temperatures increased. The use of hot and cold EGR generally increased engine exhaust emissions. However, the exhaust gas temperature decreased by 4.72% when the engine used cold EGR and 1.33% when the engine used hot EGR.